Basic Science, Epidemiology, and Screening for Anal Intraepithelial Neoplasia and Its Relationship to Anal Squamous Cell Cancer - Davis, Kurt G.; Orangio, Guy R. (Clinics in Colon and Rectal Surgery, 2018)
Despite the progress made in the reduction of squamous cell carcinoma of the cervix, the incidence of anal squamous cell carcinoma (ASCC) has been increasing since 1992. While it remains an uncommon disease, the prevalence is climbing steadily. Among human immunodeficiency virus (HIV)-infected adults, especially men who have sex with men, ASCC is one of the more common non-AIDS-defining malignancies. The precursor lesion, anal intraepithelial neoplasia (AIN), is prevalent in the HIV-infected population. More than 90% of ASCCs are related to human papilloma virus (HPV), oncogenic types (HPV 16, 18). While the biology of HPV-related intraepithelial neoplasia is consistent in the anogenital area, the natural history of AIN is poorly understood and is not identical to cervical intraepithelial neoplasia (CIN). CIN is also considered an AIDS-defining malignancy, and the methods for screening and prevention of AIN are derived from the CIN literature. This article will discuss the epidemiology of ASCC and its association with HPV and the life cycle of the HPV, and the molecular changes that lead to clearance, productive infection, latency, and persistence. The immunology of HPV infection will discuss natural immunity, humoral and cellular immunity, and how the HPV virus evades and interferes with these mechanisms. We will also discuss high-risk factors for developing AIN in high-risk patient populations with relation to infections (HIV, HPV, and chlamydia infections), prolonged immunocompromised people, and sexual behavior and tobacco abuse. We will also discuss the pre- and post-HAART era and its effect on AINs and ASCC. Finally, we will discuss the importance of anal cytology and high-resolution anoscopy with and without biopsy in this high-risk population.
Keywords: non–AIDS-defining malignancy; anal intraepithelial neoplasia; human papilloma virus; anal cytology; high-resolution anoscopy